Chapter 7 Municipal control as incumbency advantage An analysis of the AKP era - Kemahlıoğlu, Özge (Taylor & Francis, 2018)
This chapter explores whether and how the incumbent party in Turkey benefits electorally from its partisan ties at the sub-national level. This is an especially important question given the dominance of the nationally ruling party, Justice and Development Party, in Turkish electoral politics and growing concerns about the fairness of elections due to the Adalet ve Kalkinma Partisi (AKP) incumbency advantage. The chapter investigates under what conditions and how national incumbent parties benefit electorally from their partisan ties with sub-national governments. It discusses the prevalence of patronage and clientelism referred to by many scholars, who have tried to understand the mechanisms of patron-client relationships in Turkey and their consequences for the party system, the representation of citizen interests, governability and democratic accountability. The chapter provides information about Turkish local governments and their budgetary opportunities, before discussing the possibilities for political manipulation that arise from intergovernmental fiscal ties. It argues that increased municipality healthcare spending brings votes for the AKP nationally.